(3GdNjGQ GdESJQGJjLj hCKQg aj JMbjb GdejRI GdJfGaSjI (B/s - (3GdbWH, eMj GdOjfs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2012)
(3GdNjGQ GdESJQGJjLj(B- (3GdCOGA GdeGdj(B- (3GdejRI GdJfGaSjI(B- (3JMdjd hGbY GdNjGQ GdGSJQGJjLj, eDTQGJ GdCOGA GdeGdj hGdJcGdja GdQFjSjI ddTQcGJ(B- (3bjGS CKQ GdNjGQ GdGSJQGJjLj aj eDTQGJ GdCOGA GdeGdj haj YfGUQ ejRI GdcdaI GdJfGaSjI(B- (3GdESJfJGLGJ hGdJhUjGJs
(3GdeQGLY U(B.257s
Keywords: (3EOGQI GdEfJGLs; (3GdESJQGJjLjIs; (3GdEbJUGOs; (3GdefGaSIs